An efficient predictive current controller with adaptive parameter estimation in 3-ϕ inverter - Haddar Mabrouk; Allaoua Boumediene (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
In this paper, a detail design and description of a predictive current control scheme are adopted for three-phase grid-connected two-level inverter and its application in wind energy conversion systems. Despite its advantages, the predictive current controller is very sensitive to parameter variations which could eventually affected on system stability. To solve this problem, an estimation technique proposed to identify the value of harmonic filter parameter based on Model reference adaptive system (MRAS). Lyapunov stability theory is selected to guarantee a robust adaptation and stable response over large system parameter variation. The simulation results shows the efficiency of the proposed techniques to improve the current tracking performance.